Dental topographic change with macrowear and dietary inference in Homunculus patagonicus. Issue 144 (July 2020) - Li, Peishu; Morse, Paul E.; Kay, Richard F.
Abstract: Homunculus patagonicus is a stem platyrrhine from the late Early Miocene, high-latitude Santa Cruz Formation, Argentina. Its distribution lies farther south than any extant platyrrhine species. Prior studies on the dietary specialization of Homunculus suggest either a mixed diet of fruit and leaves or a more predominantly fruit-eating diet. To gain further insight into the diet of Homunculus, we examined how the occlusal surfaces of the first and second lower molars of Homunculus change with wear by using three homology-free dental topographic measures: Dirichlet normal energy (DNE), orientation patch count rotated (OPCR), and relief index (RFI). We compared these data with wear series of three extant platyrrhine taxa: the folivorous Alouatta, and the frugivorous Ateles and Callicebus (titi monkeys now in the genus Plecturocebus ). Previous studies found Alouatta and Ateles exhibit distinctive patterns of change in occlusal morphology with macrowear, possibly related to the more folivorous diet of the former. Based on previous suggestions that Homunculus was at least partially folivorous, we predicted that changes in dental topographic metrics with wear would follow a pattern more similar to that seen in Alouatta than in Ateles or Callicebus. However, wear-induced changes in Homunculus crown sharpness (DNE) and complexity (OPCR) are more similar to the pattern observed in the frugivorous Ateles and Callicebus . Based on similar wear modalities of the lower molars between Homunculus and Callicebus, we infer that Homunculus had a primarily frugivorous diet. Leaves may have provided an alternative dietary resource to accommodate fluctuation in seasonal fruiting abundance in the high-latitude extratropical environment of late Early Miocene Patagonia.